In Silico Anti-Inflammatory Activity Evaluation from Usnea misaminensis through Molecular Docking Approach - Ranggaweny Al-Ghani; Wita Putri Nirwani; Tria Nurwina Novianti; Adani Ghina Puspita Sari (Pusat Inovasi Sains, 2022)
Usnea misaminensis is an epiphytic medicinal plant from Indonesia that has several benefits, one of which is as an anti-inflammatory. This study aims to predict the ability of three compounds from Usnea misaminensis to inhibit the COX-2 enzyme as a source of prostaglandins using molecular docking. Receptors obtained from RSCB with PDB ID:5IKR were then prepared on UCSF Chimera 1.16 and the ligands (usnic acid, salizinic acid, and evernic acid) were downloaded 2D structure in .pdbqt format from PubChem. Docking simulation is done via AutoDock Vina 1.1.2 embedded in AutoDockTools 1.5.7. The docking results are visualized using PyMOL 2.5.2 and Biovia Discovery Studio Visualizer. Evernic acid showed binding energy (-6.8 kcal/mol) to the COX-2 receptor which was close to the binding energy value of the control ligand. Usnic acid and salazinic acid showed interactions with the same SER530 residue as the reference ligand. Compounds containing anti-inflammatory effects have the lowest binding energy and bind to residues as reference ligands. These results indicate that the compounds from Usnea misaminensis have potential as anti-inflammatory agents, but further research is needed to examine the potential anti-inflammatory activities.